Measuring infrastructure projects' impact on UN SDG global goals: development of an SDG impact-value chain for the infrastructure sector based on the triple bottom line. (22nd September 2021) - Mansell, Paul; Philbin, Simon P.; Broyd, Tim; Nicholson, Ian
Global grand challenges of climate change, pandemics and other sustainable development risks are threatening international societies. Six years ago, the need for urgent action was grasped by the international community in their report, 'Transforming Our World: the 2030 Agenda for Sustainable Development' (United Nations, 2015), where the 17 sustainable development goals (SDG) were adopted by 193 states at the UN General Assembly. This research study develops a theory-led value-chain impact model that enables project success to be measured against economic, social and environmental aspects, i.e., 'triple bottom line' (TBL). This integrated approach provides the infrastructure sector a way to increase the benefits realised across the TBL according to SDG language that accords with global imperatives. The study informs investment decisions and offers academics and practitioners a viable model for future development. For example, it has recently completed pilot trials and been agreed for further development to enable full-scale roll-out across the UK's Environment Agency's portfolio of projects.